Stomach Content Analysis of Puntioplites bulufrom the PLTA Koto Panjang Reservoir Kampar RegencyRiau Province - Zaharatul Isnaini; Windarti Windarti; M. Fauzi M. Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACKPuntioplites buluis a freshwater fish that inhabit the Koto Panjang Reservoir. A study aims to understand the stomach content of P.buluhas been conducted from January to March 2019. The fish was sampled 6 times,  once/ 2 weeks. There were 65 fishes captured, but 3 fishes were discharged as they had empty stomach. Stomach content was analyzedusing a volumetric method and then the Preponderance Index (IP)was calculated. Resultsshown that the main food of the fish is Crustacea 39,38460%.Based on the data obtained, it can be concluded that the food of P.buluwas various.  Keywords : fish diet, Indeks of Preponderance, gut content, volumetric method